Accurate determination of Ba isotope ratios in barite samples by LA-MC-ICP-MS. Issue 12 (11th November 2022) - Zhang, Shenghua; Zhang, Wen; Yu, Huimin; Huang, Fang; Wang, Chao; Luo, Tao; Liu, Yongsheng; Hu, Zhaochu
Abstract : A new method for in situ determination of Ba isotope ratios in barite samples by LA-MC-ICP-MS. Abstract : In this study, we present a new high-precision method to analyze Ba isotope ratios in barite samples by laser ablation multi-collector inductively coupled plasma mass spectrometry (LA-MC-ICP-MS). Barite international standard materials (NBS127, IAEA-SO-5 and IAEA-SO-6) were sintered under high pressure using a multi-anvil device to stabilize reference materials for in situ analysis of Ba isotopes in barite samples. The isobaric interference of 134 Xe and polyatomic interference on Ba isotopes were found to be insignificant, and no significant matrix effect was found between the sintered standards and natural barite samples. Small ablation spots (16–44 μm) and a low ablation frequency (1 Hz) were used in this study. This high spatial resolution mode combined with a signal smoothing device improved the analytical precision by 12.5 times compared to the results obtained without a signal smoothing device. The long-term external precision obtained for δ 137/134 BaNBS127 is 0.09‰ (2SD). Two sintered barite international standard samples (IAEA-SO-5 and IAEA-SO-6) and six natural barite samples (Ba-FJ, Ba-FRA, Ba-YN, Ba-HN, 2JS-11 and LT-1) from different areas were measured by LA-MC-ICP-MS. The δ 137/134 BaNBS127 values of these sintered barite standards and natural barite samples determined by LA-MC-ICP-MS are in good agreement with those of double-spike measurements, confirming the reliability and accuracy of the proposed method for in situ analysis of Ba isotopes in barite. Additionally, the Ba isotope ratios of natural barite samples Ba-FJ and Ba-HN were found to be homogeneous, suggesting that these references can be used as in-house reference materials for LA-MC-ICP-MS analysis of Ba isotopes.